A concentração de mercado e internacionalização das empresas do setor de saneamento básico - Pelaes Filho, Oswaldo (2019)
Increasing interdependence between countries is creating opportunities for companies to operate in other markets, not only through exports, but in a more comprehensive way, by effectively acting in the international market through direct investments, either using equity or non-equity modes. Infrastructure markets show unique characteristics due to their specific market failures that influence access to international markets. The usual determinants of general foreign investments already identified in the literature may require additional variables in the particular context of infrastructure. In this sense, this study aims to analyze the concentration of the market in the internationalization of companies in the basic sanitation sector. The choice for this theme is justified by the gap in the literature regarding the entry of infrastructure companies into emerging markets, particularly in the topic that involves the concentration of destination markets. The methodology used was based on econometrics in a study with logit regression model with logit connection applied to panel data. Results are that the main factor for the entry of foreign direct investment is the existence of a regulatory agency in operation in the municipality, since this variable is the one that maximizes the raising of foreign capital, since the fact that a municipality owns a functioning regulatory agency increases the chance of foreign direct investment by 150.20%. The role of the HHI – Herfindal Hirschman Index variable that should be controlled as closely as possible by the municipalities is not less important for the research, since the increase of HHI in one unit decreases the chance of foreign direct investment by 99.74%. It was also verified that, if the other variables are kept constant, the increase in the density of savings per link in one unit decreases the chance of foreign direct investment by 95.98%, increasing the rate by one unit increases the chance of investment foreign direct investment by 44.57% and finally that the increase of the productivity index by one unit increases the chance of foreign direct investment by 0.22%. The contribution of this thesis is the validation of determinants of foreign direct investment that are special to the infrastructure sectors, namely the fomat of the target market (concentration), along with an institutional variable already established in the literature, the regulation.